2010
DOI: 10.4103/0019-509x.63869
|View full text |Cite
|
Sign up to set email alerts
|

Reach of mass media among tobacco users in India: A preliminary report

Abstract: The reach of different media among Indian tobacco users is presented and HIV model of information dissemination may prove to be effective in tobacco control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Also, medical and para-medical graduates should be trained in tobacco cessation methods, so that the tobacco use habit can be effectively dealt with both in the private and public sectors. It was found in one of the studies that television is the single largest mass media reaching both genders and all age groups; hence a well-designed tobacco control campaign (similar to HIV awareness programs) will help curb tobacco use [19]. This finding is also supported by our study where, 92% of the participants had seen/heard anti tobacco messages in mass media instruments like newspaper, radio and television.…”
Section: Discussionsupporting
confidence: 85%
“…Also, medical and para-medical graduates should be trained in tobacco cessation methods, so that the tobacco use habit can be effectively dealt with both in the private and public sectors. It was found in one of the studies that television is the single largest mass media reaching both genders and all age groups; hence a well-designed tobacco control campaign (similar to HIV awareness programs) will help curb tobacco use [19]. This finding is also supported by our study where, 92% of the participants had seen/heard anti tobacco messages in mass media instruments like newspaper, radio and television.…”
Section: Discussionsupporting
confidence: 85%
“…Advertisement stating the ill effects of chewing tobacco products can have a better reach only via people to people or a mass people movement rather than involving any media as at least one eighth of males do to have access or see these campaigns. [10] …”
Section: Media Implicationsmentioning
confidence: 99%
“…It is a long-standing assertion that tobacco use is a health hazard on the part of the users and nonusers alike; research has shown that its continued use is attributed to lack of knowledge. 23 An empirical study on 356 freshmen categorized as ever-smokers and nonsmokers of Tokyo Metropolitan University to determine their knowledge, attitude, and practice of smoking cigarette revealed that there were significant differences between the 2 categories in terms of health and smoking, smoking perception, and knowledge on the economic impact of tobacco. 24…”
Section: Recent Literature On Smokingmentioning
confidence: 99%